The Role of Genetic Variants in the Susceptibility of Noise-Induced Hearing Loss - Chen, Xue-min; Xue, Xin-miao; Yu, Ning; Guo, Wei-wei; Yuan, Shuo-long; Jiang, Qing-qing; Yang, Shi-ming (Frontiers in Cellular Neuroscience, 2022)
Noised-induced hearing loss (NIHL) is an acquired, progressive neurological damage caused by exposure to intense noise in various environments including industrial, military and entertaining settings. The prevalence of NIHL is much higher than other occupational injuries in industrialized countries. Recent studies have revealed that genetic factors, together with environmental conditions, also contribute to NIHL. A group of genes which are linked to the susceptibility of NIHL had been uncovered, involving the progression of oxidative stress, potassium ion cycling, cilia structure, heat shock protein 70 (HSP70), DNA damage repair, apoptosis, and some other genes. In this review, we briefly summarized the studies primary in population and some animal researches concerning the susceptible genes of NIHL, intending to give insights into the further exploration of NIHL prevention and individual treatment.